Biobanks and their role in biomedical research - Mambetisaeva, Elvira (Henry Stewart Talks, 2022)
Introduction to biobanks, Types of biological samples and data used by biobanks, Services provided by biobanks, The evolution of biobanking, Types of biobanks, Specific disease-oriented biobanks, The Framingham Heart Study, Introduction to UK biobank, Living biobanks and organoid biobanks, Biobanks and drug discovery, The role of biobanks in COVID-19 research